VALIDATING A MEASURE FOR ALTRUISTIC SELF TOWARDS THE RESPONSIBLE PLATE FOOD CONSUMPTION: A MIX METHOD APPROACH - Rasool, Shahid; Mohammad Abdu Shakur, Mahani; Mughal, Yasir Hayat; Awang, Zainudin (International Journal of Business and Society, 2019)
This study intends to establish the measurement model for altruistic self-concept for plate food consumption in social marketing. The findings from earlier studies do not really suit the altruistic self-concept scale, especially in the context of socially responsible plate food consumption. Hence, this study validated the instruments of altruistic self-concept. Using the mix method pragmatism pluralism approach using 1536 respondents for quantitative study and 11 intensive interviews for qualitative study. The data were collected using self-administered questionnaire. The respondents were selected randomly using stratified sampling technique. The exploratory factor analysis procedure retained five from the total of ten items developed. The confirmatory factor analysis (CFA) procedure using IBM-SPSS-AMOS confirmed the five measuring items for altruistic self in the context of socially responsible plate food consumption. The study employed the qualitative study to verify the four sub-constructs of altruistic self-concept namely, material, psychological, time and relationship. The novelty of this study lies on the measure of altruistic self-concept construct in the lenses of consumer behavior towards socially responsible plate food consumption. The study adapted scales and validated them by using the mix method pragmatism pluralism approach. Private and publish social marketing agencies may develop the consumer altruistic towards socially responsible plate food consumption.